THE ROLE OF GAMIFICATION IN ENHANCING CONSUMER ENGAGEMENT IN E-COMMERCE PLATFORMS - Bryan Givan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research explores the role of gamification in enhancing consumer engagement on e-commerce platforms, with a focus on understanding how gamified elements influence consumer behavior, emotional connection, and long-term loyalty. A qualitative approach was employed, utilizing in-depth interviews and focus group discussions with active users of gamified e-commerce platforms. The findings reveal that gamification significantly increases user participation by tapping into intrinsic motivations such as achievement and competition, while personalized rewards and competitive features further enhance consumer engagement. Consumers also reported a strong emotional connection with platforms that incorporate gamification, which fosters greater loyalty. However, demographic factors, such as age and technological familiarity, were found to influence the effectiveness of gamification, with younger users showing greater responsiveness. The research suggests that e-commerce platforms should tailor gamified experiences based on consumer demographics and preferences to maximize engagement. Limitations of the study include a small sample size and the reliance on self-reported data, with recommendations for future research to explore the long-term effects of gamification on purchasing behavior and examine its integration with emerging technologies.